Alzheimer’s disease manifests abnormal sphingolipid metabolism - Uranbileg, Baasanjav; Isago, Hideaki; Sakai, Eri; Kubota, Masayuki; Saito, Yuko; Kurano, Makoto (Frontiers in Aging Neuroscience, 2024)
Introduction Alzheimer’s disease (AD) is associated with disturbed metabolism, prompting investigations into specific metabolic pathways that may contribute to its pathogenesis and pathology. Sphingolipids have garnered attention due to their known physiological impact on various diseases. Methods We conducted comprehensive profiling of sphingolipids to understand their possible role in AD. Sphingolipid levels were measured in AD brains, Cerad score B brains, and controls, as well as in induced pluripotent stem (iPS) cells (AD, PS, and control), using liquid chromatography mass spectrometry. Results AD brains exhibited higher levels of sphingosine (Sph), total ceramide 1-phosphate (Cer1P), and total ceramide (Cer) compared to control and Cerad-B brains. Deoxy-ceramide (Deoxy-Cer) was elevated in Cerad-B and AD brains compared to controls, with increased sphingomyelin (SM) levels exclusively in Cerad-B brains. Analysis of cell lysates revealed elevated dihydroceramide (dhSph), total Cer1P, and total SM in AD and PS cells versus controls. Multivariate analysis highlighted the relevance of Sph, Cer, Cer1P, and SM in AD pathology. Machine learning identified Sph, Cer, and Cer1P as key contributors to AD. Discussion Our findings suggest the potential importance of Sph, Cer1P, Cer, and SM in the context of AD pathology. This underscores the significance of sphingolipid metabolism in understanding and potentially targeting mechanisms underlying AD.